Endometrial Heparin-binding Epidermal Growth Factor Gene Expression And Hormone Level Changes In Implantation\r\nWindow Of Obese Women With Polycystic Ovarian Syndrome - Zulazmi Sutaji; Muhammad Azrai Abu; Nurainie Sayutti; Marjanu Hikmah Elias; Mohd Faizal Ahmad; Abdul Ghani Nur Azurah; Kah Teik Chew; Abdul Kadir Abdul Karim; Nor Haslinda Abd Aziz; Mohd Helmy Mokhtar; Reena Rahayu Md Zin; Zeti Azura Mohamed Hussein (MDPI, 2024)
Indexed by WOS/Scopus